Analisis strategi pemasaran melalui media sosial instagram dalam perspektif ekonomi Islam - Ita Rohmawati (LPMP Imperium, 2022)
Business competition through social media is increasing. This can be seen by the increasing number of social media users. Instagram is one of the social media that has a big and important influence in a business. Online marketing through social networks has developed into a very important communication system not only for producers of goods and services but also for customers. This study aims to analyze the marketing strategy of Ayunature Roromendut through Instagram social media which is reviewed from the perspective of Islamic economics. The research used is a qualitative approach research with descriptive type. Research with a case study method or approach. Ayunature Roromendut's marketing strategy uses social media Instagram. The promotional strategy carried out by Ayunature Roromendut uses special ads, endorsements, paid promote through Instagram. Ayunature Roromendut also often holds events such as product giveaways, price reductions, coupons or vouchers, and product discounts. The principle of Islamic Economics used in the promotion of Ayunature Roromendut is on the basis of consensual and no coercion from the seller to the consumer to buy the product.